Daughters of the dust - Dash, Julie (Cohen Film Collection, 1991)
At the dawn of the 20th century, a multi-generational family in the Gullah community on the Sea Islands off of South Carolina – former West African slaves who adopted many of their ancestors’ Yoruba traditions – struggle to maintain their cultural heritage and folklore while contemplating a migration to the mainland, even further from their roots. The first wide release by a black female filmmaker, DAUGHTERS OF THE DUST was met with wild critical acclaim and rapturous audience response when it initially opened in 1991. Casting a long legacy, DAUGHTERS OF THE DUST still resonates today, most recently as a major in influence on Beyonce’s video album Lemonade. Winner of the Cinematography Award and nominated for the Grand Jury Prize in the Dramatic competition at the Sundance Film Festival. Chosen for preservation by the National Film Preservation Board, USA
https://nhfpl.kanopy.com/node/4694913
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; cinéma; communication; cours; discipline; discours dominant; esclavagisme; fem3200; histoire et politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Visual Pleasure and Narrative Cinema - Mulvey, Laura (Screen, 1975)
Cet article se propose d'utiliser la psychanalyse pour découvrir où et comment la fascination du film est renforcée par des schémas de fascination préexistants déjà à l'œuvre au sein du sujet individuel et des formations sociales qui l'ont façonné. Il prend pour point de départ la façon dont le cinéma reflète, révèle et même joue sur la lecture droite et socialement établie de la différence sexuelle qui commande les images, les regards érotiques et le spectacle. Il est utile de comprendre ce qu'a été le cinéma, comment sa magie a opéré dans le passé, tout en tentant une théorie et une pratique qui remettront en cause ce cinéma du passé. La théorie psychanalytique est ainsi appropriée ici comme une arme politique, démontrant la manière dont l'inconscient de la société patriarcale a structuré la forme cinématographique.
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cinéma; cours; discipline; fem1000; fem3200; male gaze; premier cycle; privilèges; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences; sciences humaines; sofia; systèmes d'oppressions; états-unis